Impacto del umbral de etiquetado de alimentos transgénicos en el derecho a la información de los consumidores. - Bustamante Riofrío, Adriana Sofía (2024)
The present curriculum integration work focuses on conducting a comprehensive analysis of the impact of the threshold for labeling genetically modified (GM) foods in Ecuador, particularly within the framework of consumers' right to information. Like many other countries, Ecuador has implemented specific regulations governing the labeling of foods containing GM ingredients, and this work aims to explore the various dimensions and consequences of these measures. In an effort to promote transparency and enable consumers to make informed decisions, Ecuador has established specific thresholds for the presence of genetically modified organisms (GMOs) in food products. These thresholds determine when it is mandatory for a product to bear a label indicating the presence of GM ingredients. The fundamental purpose of these regulations is to provide consumers with clear and understandable information about the genetic composition of the foods they are considering purchasing. The research begins with a review of both national and international legislation related to the labeling of GM foods and, consequently, with the fundamental consumer right to access transparent and clear information. This comprehensive analysis establishes the regulatory framework that guides labeling practices in Ecuador and situates the study within the global context of food regulations. Subsequently, an empirical assessment is conducted to explore the perception of Ecuadorian consumers regarding the labeling of GM foods. This integral component involves a thorough analysis of how the information provided on labels impacts consumer purchasing decisions. The methodology includes surveys and focus groups to collect data directly from the population, allowing for a deeper understanding of the dynamics between the labeling threshold and consumer behavior. Data is collected and analyzed through surveys and focus groups to better understand the relationship between the labeling threshold and consumer decision- making. The research results shed light on the extent to which these regulations are fulfilling their purpose of providing adequate information to consumers. Furthermore, potential improvements in labeling regulations are explored, and recommendations are made to strengthen consumers' right to information in the context of GM foods in Ecuador.